2020
DOI: 10.1001/jamasurg.2020.2713
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Surgical Mortality and Complications Among Patients With and Without Coronavirus Disease 2019 (COVID-19) in Italy

Abstract: IMPORTANCE There are limited data on mortality and complications rates in patients with coronavirus disease 2019 (COVID-19) who undergo surgery. OBJECTIVE To evaluate early surgical outcomes of patients with COVID-19 in different subspecialties. DESIGN, SETTING, AND PARTICIPANTS This matched cohort study conducted in the general, vascular and thoracic surgery, orthopedic, and neurosurgery units of Spedali Civili Hospital (Brescia, Italy) included patients who underwent surgical treatment from February 23 to Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
367
10
26

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(453 citation statements)
references
References 33 publications
26
367
10
26
Order By: Relevance
“…The Meta-Analysis showed that the prevalence of comorbidity among surgical patients was with COVID-19 was 18% (95% CI: 10 to 25) which is in line with the results of included studies (21,23,29,49,90,91,95). The subgroup analysis showed that dementia was the most prevalent comorbidity followed by hypertension and Diabetes Mellitus.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The Meta-Analysis showed that the prevalence of comorbidity among surgical patients was with COVID-19 was 18% (95% CI: 10 to 25) which is in line with the results of included studies (21,23,29,49,90,91,95). The subgroup analysis showed that dementia was the most prevalent comorbidity followed by hypertension and Diabetes Mellitus.…”
Section: Discussionsupporting
confidence: 80%
“…The Meta-Analysis showed that the pooled mean duration of hospitalization was 10.55 (95% con dence interval (CI): 8.08 to 13.03) which is comparable with the ndings of the included studies (21,29,38,39,52,(89)(90)(91)96).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…46 The risk of perioperative complications associated with COVID-19 could be significant, and profoundly affect postoperative mortality and complication rates. [49][50][51][52] This may influence future considerations regarding preoperative testing, but ideally, if it does not worsen postoperative patient outcomes, the COVID-19 status of surgical patients should be determined before surgery. 53 Where this is not possible, it is key to know which patients pose the highest risk, including those more likely to have been exposed to COVID-19 due to their profession.…”
Section: Perioperative Considerationsmentioning
confidence: 99%
“…Infection with the causative virus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been associated with considerable postoperative mortality and morbidity for surgical patients. [1][2][3] The global backlog of operations resulting from the temporary suspension of elective surgery could take close to a year to resolve. 4 Although both Australia and New Zealand have experienced a relatively low COVID-19 caseload on an international scale, 5 surgical systems within both countries have still been affected.…”
Section: Introductionmentioning
confidence: 99%